Pairing limb posture feedback with an ankle exoskeleton to augment limb propulsion - Steven A. Thompson; Emily E. Foley; Jason R. Franz; Gregory S. Sawicki; Michael D. Lewek (PLoS ONE, 2025)
Limb propulsion deficits are common in a variety of clinical populations and may arise from a decreased plantarflexor moment and/or decreased trailing limb angle (TLA). Ankle exoskeletons (EXOs) can augment plantarflexor moment, but observations of a concurrently reduced TLA has limited the conversion of increased plantarflexor moment to increased propulsion in people following stroke. The purpose of this study was to assess the interaction of unilateral EXO (plantarflexor) assistance and TLA feedback on gait propulsion, joint mechanics, and margins of stability. Ten young, unimpaired individuals walked on an instrumented treadmill with the EXO worn but unpowered to obtain baseline peak TLA. Participants then walked with visual feedback of TLA while attempting to match a target peak TLA of baseline-5°, baseline, or baseline+5° in random order. For each target TLA, participants walked with three EXO plantarflexor torque magnitudes, with peak assistance proportional to bodyweight (0%, 15%, and 35% bodyweight) in random order. Propulsive impulse significantly increased as peak TLA increased but was not affected by EXO assistance. Higher EXO assistance resulted in a proximal-to-distal shift in positive mechanical work performed by the lower limb, observed as an increase in the relative contribution of the ankle to total ankle and hip positive mechanical work. Increased TLA significantly reduced the magnitude of the anteroposterior margin of stability at toe-off, while higher EXO assistance yielded larger anteroposterior margins of stability. Margins of stability in the mediolateral direction were not affected by TLA or EXO assistance. This study highlights the potential for increasing propulsion through feedback of TLA, but with potential negative impacts to stability. For populations with deficits in plantarflexor moment, the use of visual feedback to prevent a reduction in TLA while walking with ankle EXOs may allow conversion of joint benefits to benefits in limb propulsion.